Peranan Sistem Swampy Forest Pada Pengolahan Air Asam Tambang Dari Kegiatan Pertambangan Batubara - Noor, Ihsan; Arifin, Yudi Firmanul (Lambung Mangkurat University Press, 2024)
Most coal mining activities in South Kalimantan apply the open pit method, which has the potential to produce acid mine drainage. As wastewater from coal mining activities, acid mine water has high acidity and metal content. Mitigation of the handling of acid mine drainage can be grouped into two processing techniques: active processing using conventional methods by neutralizing the acidity by applying quicklime. Still, in the end, this processing is considered very expensive, and passive processing is relatively cheaper but has limited processing capacity, so development with the Swampy Forest system is required. The acid mine drainage that has occurred and which has been collected in the post-mining lake is then channeled to the Swampy Forest system processing pond, which has been given organic material, and the specified types of hyperaccumulator grass and trees have been planted to change the water quality which does not meet the quality standard values to meet it. quality standard values under applicable regulations. The Swampy Forest system is proven to significantly improve water quality to meet applicable regulatory compliance requirements with a cheaper and environmentally friendly process.